Blunt Versus Penetrating Neck Trauma: A Retrospective Cohort Study. (7th September 2020) - Forner, David; Noel, Christopher W.; Guttman, Matthew P.; Haas, Barbara; Enepekides, Danny; Rigby, Matthew H.; Nathens, Avery B.; Eskander, Antoine
Abstract : Objectives/Hypothesis: Despite being common, neck injuries have received relatively little attention for important quality of care metrics. This study sought to determine the association between blunt and penetrating neck injuries on mortality and length of stay, and to identify additional patient and hospital‐level characteristics that impact these outcomes. Study Design: Retrospective cohort study utilizing the American College of Surgeons Trauma Quality Improvement Program database. Methods: Adult patients (≥18) who sustained traumatic injuries involving the soft tissues of the neck between 2012 and 2016 were eligible. Multiple imputation was used to account for missing data. Logistic regression and negative binomial models were used to analyze 1) in‐hospital mortality and 2) length of stay respectively while adjusting for potential confounders and accounting for clustering at the hospital level. Results: In a cohort of 20, 285 patients, the crude mortality rate was lower in those sustaining blunt neck injuries compared to penetrating injuries (4.9% vs. 6.0%, P  < .01), while length of hospital stay was similar (median 9.9 vs. 10.2, P = 0.06). In adjusted analysis, blunt neck injuries were associated with a reduced odds of mortality during hospital admission (odds ratio: 0.66, 95% confidence intervals [0.564, 0.788]), as well as significant reductions in length of stay (rate ratio: 0.92, 95% confidence intervals [0.880, 0.954]). Conclusions: Blunt neck injuries are associated with lower mortality and length of stay compared to penetrating injuries. Areas of future study have been identified, including elucidation of processes of care in specific organs of injury. Level of Evidence: Level 3 Laryngoscope, 131:E1109–E1116, 2021